2007
DOI: 10.1051/forest:2006082
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of early selection for rotation-aged wood quality traits in radiata pine

Abstract: -A total of 360 bark-to-bark-through-pith wood strips were sampled at breast height from 180 trees in 30 open-pollinated families from two rotation-aged genetic trials to study inheritance, age-age genetic correlation, and early selection efficiency for wood quality traits in radiata pine. Wood strips were evaluated by SilviScan and annual pattern and genetic parameters for growth, wood density, microfibril angle (MFA), and stiffness (modulus of elasticity: MOE) for early to rotation ages were estimated. Annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 18 publications
6
32
0
3
Order By: Relevance
“…Studies on growth and wood density in different Pinus species revealed that genetic age-age correlation >0.8 is generally achieved from the age of 10-12 years (Hannrup and Ekberg 1998;Gwaze et al 2000;Wu et al 2007;Bouffier et al 2008). It varies greatly with environmental conditions, and in Pinus radiata, this level of correlation can be reached as soon as 2-5 years in certain sites (Gwaze et al 2000;Wu et al 2007). Matheson et al (2002) showed that genetic age-age correlations in Pinus radiata also vary with the genetic background with higher correlations in presence of inbreeding.…”
Section: Foreseen Evolutionary Impact Of Common Forestry Practicementioning
confidence: 99%
“…Studies on growth and wood density in different Pinus species revealed that genetic age-age correlation >0.8 is generally achieved from the age of 10-12 years (Hannrup and Ekberg 1998;Gwaze et al 2000;Wu et al 2007;Bouffier et al 2008). It varies greatly with environmental conditions, and in Pinus radiata, this level of correlation can be reached as soon as 2-5 years in certain sites (Gwaze et al 2000;Wu et al 2007). Matheson et al (2002) showed that genetic age-age correlations in Pinus radiata also vary with the genetic background with higher correlations in presence of inbreeding.…”
Section: Foreseen Evolutionary Impact Of Common Forestry Practicementioning
confidence: 99%
“…Age-age genetic correlations have been reported in loblolly pine and were generally very high for younger aged trees compared with trees 15 or 20 years old (LAM-BETH et al, 1983;BALOCCHI et al, 1993;GWAZE et al, 1998GWAZE et al, , 2000SVENSSON et al, 1999;LAMBETH and DILL, 2001;. However, Age-age correlation values were usually low to moderate for older aged trees in the Pinaceae at more than half the rotation age (WU et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, testing the age-age correlation of economically important traits is critical to determining the optimal age for early forward selection for breeding purpose and backward selection for establishment of seed orchards (LAMBETH et al, 1983;WU et al, 2007;KUMAR and LEE, 2002). Many efforts have also been made to evaluate the efficiency of early selection for growth traits (LAMBETH, 1980;MAGNUSSEN, 1988;BURDON, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The samples are scanned from pith to bark using X-ray densitometry, X-ray diffractometry and image analysis to measure or predict a range of properties. Different researchers have opted for using an average core value (e.g., Apiolaza et al, 2005), modelling the evolution of the trait (e.g., Apiolaza and Garrick, 2001;Isik et al, 2008;Zamudio et al, 2002) or calculating age-age correlations for area-weighted averages (e.g., Dungey et al, 2006;Kumar et al, 2006;Wu et al, 2007). These studies have assumed that an appropiate goal for a breeding program is to improve an average value for the trait at rotation age.…”
Section: Phenotypic Informationmentioning
confidence: 99%